Service quality, perceived value and behavioral intentions among highly and lowly identified baseball consumers across nations. Issue 1 (9th September 2019) - Ma, Shang Chun; Kaplanidou, Kyriaki
Abstract : Purpose: The purpose of this paper is to understand how team identification and country influence professional baseball team spectators' evaluations of service quality factors, perceived value and future behavioral intentions. Design/methodology/approach: Data were collected online from sports consumers of the Chinese Professional Baseball League (CPBL) in Taiwan ( n = 600) and Major League Baseball in the USA ( n = 460). A regression-based estimation method (PROCESS) and structural equation modeling approach were used to assess the relationships. Findings: Both direct and indirect (via perceived value) effects of most service quality factors (schedule convenience, economic consideration, game amenities, ticket service and venue quality) on behavioral intentions are stronger for lowly than for highly identified CPBL fans. The indirect effect of home team on behavioral intentions is stronger for the lowly identified CPBL fans. The direct effect of game amenities and the indirect effect of venue quality (via perceived value) on behavioral intentions are stronger for the highly identified MLB fans. The indirect effect of opposing team and economic consideration is stronger for the lowly identified MLB fans. The positive relationship between venue quality and perceived value is stronger for the USA than for Taiwan fans. The relationships between game amenities and perceived value and between perceived value and behavioral intention are perceived to be invariant between fans from the two countries. Taiwan fans' behavioral intentions tend to be directly and indirectly affected by service quality factors, whereas US fans' behavioral intentions tend to be indirectly affected by service quality factors. Originality/value: The study provides empirical evidence of the moderating role of team identification associated with the relationships between separate service quality factors, perceived value and behavioral intentions among consumers of a professional spectator sports in two different countries.